THERAPEUTIC EFFICACY OF MAGNESIUM SULPHATE ON NEUROLOGICAL OUTCOME OF NEONATES WITH SEVERE BIRTH ASPHYXIA - Nisar Khan Sajid; Muhammad Junaid; Saeed Ahmed (Journal of University Medical & Dental College, 2018)
ABSTRACT:BACKGROUND: In neonates, birth asphyxia is a serious condition. It results in high risk of morbidity and mortality. It is also associated with permanent neuro developmental deﬁcits among survivors. OBJECTIVES: The main objective of the study is comparing the eﬃcacy of intravenous magnesium sulphate (MgSO4) with placebo in neonates with severe birth asphyxia in terms of neurological outcome. METHOD: A total of 66 subjects were recruited in Pediatrics Medicine Unit-II, DHQ Hospital, Faisalabad from April 2011 to December 2011. Neonates divided into two groups A & B (33 patients in each group) with history of birth asphyxia. Neonates of group-A were given MgSO4 through I.V route(3 doses 250 mg/kg/dose, 24 hours interval) and group B received normal saline(3 doses 1 ml/kg/dose 24 hours interval). During stay in NICU all Neonates were regularly neurologically assessed. RESULTS: Mean age (hour) was observed 2.82±1.35 and 3.24±1.60 in both A and B groups respectively. Total of 18(54.5%) subjects in group A and 19(57.6%) subjects in group B had 37-38 weeks while, 15(45.5%) and 14(42.4%) subjects had 39-40 weeks of gestational age respectively. At discharge time, neurological ﬁndings (neonatal reﬂexes) were improved in 25(75.8%) subjects in A group and 15(45.4%)subjects in B group. Statistically signiﬁcant P value was found to be 0.002 for oral feed (sucking). Normal CT brain was seen in 28(84.9%) subjects in group A and 17(51.5%) subjects in group B. CONCLUSION: Neurological outcome at discharge were improved with the treatment of postnatal I/V magnesium sulfate in neonates with severe birth Asphyxia when given early after birth having severe perinatal asphyxia.